2019
DOI: 10.1007/s13280-019-01244-4
|View full text |Cite
|
Sign up to set email alerts
|

Acid rain and air pollution: 50 years of progress in environmental science and policy

Abstract: Because of its serious large-scale effects on ecosystems and its transboundary nature, acid rain received for a few decades at the end of the last century wide scientific and public interest, leading to coordinated policy actions in Europe and North America. Through these actions, in particular those under the UNECE Convention on Long-range Transboundary Air Pollution, air emissions were substantially reduced, and ecosystem impacts decreased. Widespread scientific research, long-term monitoring, and integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
124
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 285 publications
(125 citation statements)
references
References 32 publications
0
124
0
1
Order By: Relevance
“…The industrial nations had designed tall stacks to disperse the pollutants without considering possible effects outside their jurisdiction. The combination of the science and political background is described in detail by Grennfelt et al [57]. An earlier description of the political background in the UK by Rose [65] provides further insights and is typical of the large number of publications on the politics of acid rain.…”
Section: S Acid Rainmentioning
confidence: 99%
See 1 more Smart Citation
“…The industrial nations had designed tall stacks to disperse the pollutants without considering possible effects outside their jurisdiction. The combination of the science and political background is described in detail by Grennfelt et al [57]. An earlier description of the political background in the UK by Rose [65] provides further insights and is typical of the large number of publications on the politics of acid rain.…”
Section: S Acid Rainmentioning
confidence: 99%
“…The scale of effects of pollutants on ecosystems quantified at the turn of the twenty-first century showed that 24% of global forests were exposed to phytotoxic exposures of ozone [100]. The development of the Critical Loads approach and integrated assessment methods proved valuable instruments in the development of policies to maximize the ecological benefits of control measures within the LRTAP Convention [57].…”
Section: Eutrophication: the Effects Of Nitrogen Deposition On Ementioning
confidence: 99%
“…The pH of rainwater drops and becomes more acidic due to atmospheric emissions of air pollutants, almost exclusively caused by destructive human activities, in particular the burning of fossil fuels, industrial and agricultural activities, and car exhaust fumes. The phenomenon of wet deposition with high concentrations of sulphur dioxide and nitrogen oxides has been defined as acid rain [ 1 , 2 , 3 ]. Rain is categorised as acid rain when its pH is 5.6 or below.…”
Section: Introductionmentioning
confidence: 99%
“…Rain is categorised as acid rain when its pH is 5.6 or below. The acid rain phenomenon remains topical, despite extensive research and continuous monitoring of acid deposition and air pollution being carried out for at least half a century, following several cross-border agreements, protocols, and policies [ 1 ]. Although emissions have decreased significantly in Western European countries, North America, and some others, Southwest China and Southeast Asia countries are among the worst affected areas [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…These pollutants are harmful to human health and to the environment. [18][19][20][21] They also prevent the use of more advanced emission control systems in motor vehicles, e.g. for limiting NO x emissions.…”
Section: Introductionmentioning
confidence: 99%